'House is not universal. House is hyper-specific': dance music sequences and affect in 120 BPM and Eden. (3rd April 2022) - Gledhill, Tom
ABSTRACT: Dance floor sequences in narrative film are often directly informed by an oversimplified heteronormative interpretation of the Peace Love Unity and Respect ethos. Among the growing body of films that have dance floor sequences, 120 BPM (2017) stands in direct opposition to this construction. After an initial discussion of how identity and dance music intersect in 120 BPM and the contemporaneous French film Eden (2014), this article will centrally focus on the way the former film subverts three core features that are prevalent in the latter: the centrality of the DJ, a superficial engagement with the political dimension of dance music culture and a literal interaction between the dance floor space and the rest of the narrative. I will argue that by subverting these structural markers, 120 BPM not only distances itself stylistically from Eden, but also locates the club as a specifically queer space. Simultaneously, this paper will engage with the role of affect within these sequences. By illustrating how 120 BPM combines both emotional and affective strategies, I will argue that the film's presentation of the dance floor space contextualizes how dance music culture and HIV/AIDS activism relate to one another.